2010
DOI: 10.1139/b10-026
|View full text |Cite
|
Sign up to set email alerts
|

Localization of endophyticUndifilumfungi in locoweed seed and influence of environmental parameters on a locoweed in vitro culture system

Abstract: Endophytic Undifilum oxytropis (Q. Wang, Nagao & Kakish) Pryor, Creamer, Shoemaker, McLain-Romero, & Hambleton found within toxic locoweeds ( Astragalus and Oxytropis spp.) produces the alkaloid swainsonine, which is responsible for locoism in grazing animals. We sought to determine the location of U. oxytropis within locoweed seed, develop endophyte free plants, and assess the influence of environmental stresses on locoweed and endophyte cultures. Undifilum was identified within the parenchyma layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 25 publications
5
83
0
Order By: Relevance
“…This colonization is consistent with transmission of A.U. oxytropis, which is maternally transmitted through seed (Oldrup et al 2010). Braun et al (2003) found that slow growing Alternaria sect.…”
Section: Sphaerophysa Salsula Oxytropis Glabra Astragalus Variabilissupporting
confidence: 74%
See 2 more Smart Citations
“…This colonization is consistent with transmission of A.U. oxytropis, which is maternally transmitted through seed (Oldrup et al 2010). Braun et al (2003) found that slow growing Alternaria sect.…”
Section: Sphaerophysa Salsula Oxytropis Glabra Astragalus Variabilissupporting
confidence: 74%
“…They can be readily isolated from leaves, petioles, stems, flowers and seed (Braun et al, 2003). The fungi are vertically transmitted through seed, but found only in the seed coat and underlying layer (Oldrup et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, seeds maintained at higher temperatures, at low relative humidity and for longer periods of time were less likely to retain the infection, presumably associated with loss of fungal viability on the seed (do Valle Ribeiro, 1993). However, the impact of temperature is not universal: Oldrup et al (2010) noted that 80% of locoweed seed maintained in uncontrolled warehouse conditions over 40 years retain Undifilum endophyte infection (Oldrup et al, 2010).…”
Section: Physiological Cost Of Symbionts At Different Temperaturesmentioning
confidence: 99%
“…The inhibitory properties on α-mannosidase have been exploited for the development of swainsonine as an anticancer drug, which has been impaired by reason of undesirable side effects [331,332]. Finally, it is interesting to note that plants of A. lentiginosus and Oxytropis sericea germinated from the embryo, which is not colonized by endophytes, were found to be fungus free and did not contain swainsonine [333]. This evidence strongly supports the hypothesis that actually its occurrence in plants may entirely derive from biosynthesis by endophytic fungal strains.…”
Section: Other Alkaloidsmentioning
confidence: 99%